Design of a new organizational structure of the Corporación Peruana de Aeropuertos y Aviación Comercial S.A. for the achievement of a strategic plan (SCIÉNDO INGENIUM, 2022)
The objective of this research was to determine to what extent the evolution of organizational design allows the achievement of strategic plans in an entity responsible for air transport. This research was applied, descriptive, transversal of correlational design, being the census population 20 directors of CORPAC. The survey technique was used, for which the organizational design questionnaires and the strategic planning questionnaire were adapted. Finally, a relationship was found between the design of a new organizational structure and the achievement of the strategic plan in CORPAC S.A (Rho = 0.802, p = 0.000, alpha = 0.05) meaning that the fulfillment of the strategic plans is linked to a design of a new organizational design. The policy of evolution of organizational designs to achieve the strategic plans that are adjusted annually in the face of changes in the internal and external environment is necessary in terms of the extension of the company that is all of Peru and the realities of airports and air traffic are changing, which makes necessary the change of organizational structure more technically known as organizational design.
Keywords: Design; organic structure; Corporación Peruana de Aeropuertos y Aviación Comercial S.A.; strategic Plan